Copying Rules Motivation to Generate Wh-Questions in Standard Malay in Minimalist Program: (Motivasi Rumus Salin dalam Penjanaan Ayat Tanya Bahasa Melayu dalam Program Minimalis) (Jurnal Bahasa, 2020)
Previous theories prior to the Minimalist Program, such as the Government Binding Theory (Chomsky, 1981) and Principles and Parameters, the variation of sentence structures are explicated via the rule move-α, whereby it moves any constituents to any position in a sentence and leaves behind a trace (t) in its antecedent/operator-trace chain. Within the Minimalist Program approach, which was eclectically derived from the ideas in Chomsky (1995), Marantz (1995) and Radford (2009), the rule move-α has been dropped. Sentence generation and sentence varieties are generated via copying rules instead. This study analyses the motivations that support copying rules in the generation of wh-questions and yes-no questions. This study employs the qualitative method and the data for this study was collected through native speakers' introspection. Subsequently, the data were referred to two informants who are native speakers of standard Malay to determine their grammaticality. This study finds that feature [+/-wh] and the edge feature; namely [+comp], [+/-wh], [+/-focus],] and [+/-in situ] are features that motivated or were barriersto the generation of wh- and yes-no questions and their varieties in the Malay language.Keywords: Minimalist Program, copying rules, features, wh- questions, yes-no questions